Объяснение:
1) (1/3-11/3) : (0,(5))=(-10/3): (-5/9)=(-10/3)*(-9/5)=(-2)*(-3)=6
*0,(5)=5/9
2) 0,(11)-0(23) :2/33=(11/99-23/99) : 2/33= (-12/99) *33/2= (-6/3)*1=-2
*0,(11)=11/99
*0,(23)=23/99
3)0,(4) : (1- 5/7)=4/9 : 2/7=4/9 * 7/2=2/9*7=14/9= 1 5/9= 1,(5)
*0,(4)=4/9
4) 1,(5)*5/7*6/5= 14/9*5/7*6/5=16/45= 0,3(5)
*1,(5)=14/9
Объяснение:
1) (1/3-11/3) : (0,(5))=(-10/3): (-5/9)=(-10/3)*(-9/5)=(-2)*(-3)=6
*0,(5)=5/9
2) 0,(11)-0(23) :2/33=(11/99-23/99) : 2/33= (-12/99) *33/2= (-6/3)*1=-2
*0,(11)=11/99
*0,(23)=23/99
3)0,(4) : (1- 5/7)=4/9 : 2/7=4/9 * 7/2=2/9*7=14/9= 1 5/9= 1,(5)
*0,(4)=4/9
4) 1,(5)*5/7*6/5= 14/9*5/7*6/5=16/45= 0,3(5)
*1,(5)=14/9